Gut Microbiome Alterations in Patients With Carotid Atherosclerosis - Chen, Jingfeng; Qin, Qian; Yan, Su; Yang, Yang; Yan, Hang; Li, Tiantian; Wang, Lin; Gao, Xinxin; Li, Ang; Ding, Suying (Frontiers in Cardiovascular Medicine, 2021)
Carotid atherosclerosis (CAS) is the reflection of systemic atherosclerosis and the main pathological process of cardiovascular disease (CVD), including the carotid intima-media thickness, carotid plaque, and carotid stenosis. Accumulating evidence indicates that the gut microbiota plays an important role in CVD and gut-brain disorders, yet the association between the composition and metabolites of the gut microbiome and CAS has not been studied comprehensively. We performed a gut microbiome genome-wide association study in 31 patients with CAS and 51 healthy controls by using whole-genome shotgun sequencing. We firstly found many risk factors (WC, BMI, DBP, SBP, FBG, HbA1c, TC, TG and LDL) and inflammation markers (WBC and NEUT) in CAS group were significantly higher than that in healthy controls. Then 21 species and 142 pathways were enriched in CAS group and 10 species and 1 pathway were enriched in healthy controls, where Bacteroides eggerthii, Escherichia coli, and Klebsiella pneumoniae in CAS group and Parabacteroides unclassified, Prevotella copri, Bacteroides sp 3_1_19, and Haemophilus parainfluenzae in healthy group had a higher abundance than other species. Finally, we found that most of gut microbiomes and microbial pathways enriched in CAS group had a significant positive correlation with clinical characteristics, while those enriched in healthy controls had a significant negative correlation with clinical characteristics except HDL. Also the association between gut microbiomes and some microbial pathways (short-chain fatty acids, lipopolysaccharide, and menaquinol biosynthesis) had been identified. Our results indicate that there may exist a cyclic path of elevating the circulating concentrations of trimethylamine-N-oxide (TMAO) in CAS group, while a route of reducing the TMAO level in healthy controls.